A novel fluorescent functional monomer as the recognition element in core–shell imprinted sensors responding to concentration of 2, 4, 6-trichlorophenol. Issue 11 (6th February 2018) - Ren, Baixiang; Qi, Huan; Li, Xiuying; Liu, Lihui; Gao, Lin; Che, Guangbo; Hu, Bo; Wang, Liang; Lin, Xue
Abstract : We have demonstrated a molecularly imprinted sensor with a fluorescent functional monomer instead of the traditional functional monomers to detect 2, 4, 6-TCP. Abstract : We have demonstrated a fluorescent functional monomer instead of the traditional functional monomers for molecularly imprinted sensors. The sensors were firstly used to selectively detect 2, 4, 6-trichlorophenol (2, 4, 6-TCP) by solid fluorescence detection without a dispersion solution. Moreover, the selectivity and anti-interference ability of the SiO2 @dye-FMIPs sensor meet the requirements of a fluorescent sensor. The novel fluorescent monomer introduced into MIP is no longer just a fluorophore without recognizing ability. The fluorescence intensity of SiO2 @dye-FMIPs showed a linear response to 2, 4, 6-TCP concentration in the range of 0–100 nM with a detection limit of 0.0534 nM. We could also demonstrate that such a system can not only get rid of the confines of traditional functional monomers and detection manner, but also improved the applications of MIPs sensors in sensing systems.